New Forms of Land Grabbing Due to the Bioeconomy: The Case of Brazil - Cudlínová, Eva; Giacomelli Sobrinho, Valny; Lapka, Miloslav; Salvati, Luca (MDPI AG, 2020)
The present study discusses new forms of land grabbing related to biofuel production in the light of bioeconomic development. With a specific focus on Brazil, this article debates whether biofuel production is associated with (i) an expansion of agricultural land use—regarded as a process of unsustainable crop intensification or (ii) an increase in crop yield, driven by technical innovation with stable land use—intended as a form of sustainable intensification. We conclude that, in the case of Brazil, the current bioeconomy cannot be assumed to be environmentally sustainable. Starting from Brazil’s experience, the (apparent and latent) relationship between bioeconomy and land grabbing requires a refined investigation in both wealthier and emerging economies, with the aim of proposing effective strategies to achieve truly sustainable development in the primary sector.
Keywords: land grabbing; bioeconomy; sustainable intensification; biofuels; sugar cane; ethanol